Einführung in das Mittelhochdeutsche - Hennings, Thordis (De Gruyter, 2012)
This introductory work is now presented as a revised and improved third edition. It gives students the basic knowledge of Middle High German that is required for successful completion of a first degree in mediaeval and German studies. This volume can be used as a textbook for a relevant basic course but is also appropriate for personal study. Reliable introductory work for basic university courses in mediaeval and German studies Provides comprehensive grounding in Middle High German Also suitable for personal study
Literaturverzeichnis: Seite 232-235
Keywords: Lehrbuch; Mittelhochdeutsch